Hyperfunctioning thyroid cancer: a five-year follow-up - Azevedo,Monalisa Ferreira (2010)
Differentiated thyroid cancer rarely occurs in association with hyperfunctioning nodules. We describe a case of a 47-year-old woman who developed symptoms of hyperthyroidism associated with a palpable thyroid nodule. Thyroid scintigraphy showed an autonomous nodule, and fine-needle aspiration biopsy was suggestive of papillary carcinoma. Laboratorial findings were consistent with the diagnosis of hyperthyroidism. The patient underwent thyroidectomy and a papillary carcinoma of 3.0 x 3.0 x 2.0 cm, follicular variant, was described by histological examination. The surrounding thyroid tissue was normal. Postoperatively, the patient received 100 mCi of 131I, and whole body scans detected only residual uptake. No evidence of metastasis was detected during five years of follow-up. Hot thyroid nodules rarely harbor malignancies, and this case illustrated that, when a carcinoma occurs the prognosis seems to be very good with no evidence of metastatic dissemination during a long-term follow-up.